2014
DOI: 10.1007/s10545-014-9737-0
|View full text |Cite
|
Sign up to set email alerts
|

Pain: a prevalent feature in patients with mucopolysaccharidosis. Results of a cross‐sectional national survey

Abstract: With or without intellectual disabilities, many MPS patients experience pain. We recommend that standardized pain assessments are included in the regular follow-up program of patients with MPS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 40 publications
(50 reference statements)
1
44
0
1
Order By: Relevance
“…Impaired mobility is prevalent in MPS patients, with many individuals requiring walking aids or a wheelchair [11, 1315] (Fig. 2).…”
Section: How Does Mps Affect Hrqol?mentioning
confidence: 99%
See 3 more Smart Citations
“…Impaired mobility is prevalent in MPS patients, with many individuals requiring walking aids or a wheelchair [11, 1315] (Fig. 2).…”
Section: How Does Mps Affect Hrqol?mentioning
confidence: 99%
“…Joint abnormalities can result in poor shoulder ROM, wrist weakness, stiffness or changes in mobility which in turn affect simple ADL tasks such as dressing, washing and eating [16]. Pain may arise from joint defects, infections including otitis media, neurological involvement and neuropathic signals arising in the brain, increased intracranial pressure, spinal cord compression, or carpal tunnel syndrome [13, 15, 17]. Fatigue, the result of impaired cardiopulmonary function, can produce stress, anger, frustration, and potentially depression [18].…”
Section: How Does Mps Affect Hrqol?mentioning
confidence: 99%
See 2 more Smart Citations
“…They concluded that many of these instruments have demonstrated that QoL is negatively impacted in patients with MPS. Overall, the most affected QoL domains were pain/discomfort [23] and mobility; problems with self-care or activities of daily living were also critical factors. Also, wheelchair use, unemployment, poor endurance, and poor pulmonary function were also associated with worse QoL [2435].…”
Section: Introductionmentioning
confidence: 99%